Eksplorasi Zakat Saham Dalam Tinjauan Ekonomi Islam - Sitti Muallimah; Agustinar; Asnita, Dessy (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
This research aims to find out how Zakat on Shares is from an Islamic Economic Perspective? And what is the potential for Zakat on shares as a source of income for the community? The method used is a qualitative descriptive approach. The results obtained are that in a review of Islamic economics, share zakat is one mechanism for implementing the principle of a more equitable distribution of wealth in society, while supporting sustainable economic development. Exploration of share zakat in Islamic economics is a relevant and important concept in the development of an economic system based on Islamic principles. The potential for share zakat in Indonesia has increased, but this increase is not commensurate with the number of investors and the population of Indonesia. One of the causes is the low level of understanding of share zakat among investors, so this education is a necessity. Share Zakat has great potential for the people. The more people who invest in sharia shares, the greater the potential for collecting zakat on shares, which includes providing a wider selection of sharia shares, supporting companies that comply with sharia principles, and holding educational programs for Muslims about investing in accordance with sharia.